2021
DOI: 10.1111/jam.15290
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of a rare two‐component lantibiotic, amyloliquecidin GF610 produced by Bacillus velezensis , using a combination of culture, molecular and bioinformatic analyses

Abstract: Aim: To detect and characterize novel lantibiotics from a collection of Bacillus spp. using a multifaceted analytical approach. Methods and Results: A previously completed microassay identified 45 Bacillus isolates with anti-Listeria activity. The isolates were PCR screened using degenerate primers targeting conserved sequences in lanM-type lantibiotics. B. velezensis GF610 produced a PCR product whose sequence, along with genome mining and bioinformatics, guided the liquid chromatographic analysis of strain's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Although many operational Group B. amyloliquefaciens strains are known to produce antimicrobial compounds ( Lv et al, 2020 ; Gerst et al, 2021 ), we sought to discover the direct protective effects of ADS024 and DSM7 in toxin-treated human colonic epithelial cells. C. difficile toxins kill human colonic epithelial cells via apoptosis ( Fiorentini et al, 1998 ; Brito et al, 2002 ), leading to intestinal injury.…”
Section: Resultsmentioning
confidence: 99%
“…Although many operational Group B. amyloliquefaciens strains are known to produce antimicrobial compounds ( Lv et al, 2020 ; Gerst et al, 2021 ), we sought to discover the direct protective effects of ADS024 and DSM7 in toxin-treated human colonic epithelial cells. C. difficile toxins kill human colonic epithelial cells via apoptosis ( Fiorentini et al, 1998 ; Brito et al, 2002 ), leading to intestinal injury.…”
Section: Resultsmentioning
confidence: 99%
“…Amyloliquecidin gene clusters within the SZA14 and SZA16 genomes are present in contigs 14 and 9, respectively. While Gerst et al ( 2022 ) in their study reported the presence of amyloliquecidin in contig 19. So far, the gene cluster for lantibiotic amyloliquecidin has been reported in four strains from different locations: Bacillus spp .…”
Section: Discussionmentioning
confidence: 86%
“…Amyloliquecidin is a relatively new two-component (α and β peptides) lantibiotic (Gerst et al 2022 ). It is active against most of the tested gram-positive species, which include Listeria monocytogenes, Clostridium sporogenes , Clostridioides difficile, S. aureus (Van Staden et al 2016 ) , and Alicyclobacillus acidoterrestri (Gerst et al 2022 ) . Amyloliquecidin gene clusters within the SZA14 and SZA16 genomes are present in contigs 14 and 9, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti- Listeria molecule of SF214 is, therefore, highly specific and for this reason peculiar with respect to other AMPs that have a broad spectrum of action [ 1 3 ]. Examples are the recently discovered Amyloliquecidic GF610 of B. velenzensis [ 17 ] and a molecule produced by B. amyliquefaciens JFL21 [ 18 ], both active against Listeria but also against several Gram-positives and the latter also against some fungal pathogens. For its specificity and its proteinaceous nature the SF214 molecule will be therein indicate as s pecific a nti- Listeria m onocytogenes p eptide (SAMP) and all further analyses performed with L. monocytogenes ATCC 7644 as the target bacterium.…”
Section: Resultsmentioning
confidence: 99%